Mother knows best : a novel of suspense - Peikoff, Kira (Crooked Lane, 2019)
"Claire Abrams's dreams became a nightmare when she passed on a genetic mutation that killed her little boy. Now she wants a second chance to be a mother, and finds it in Robert Nash, a maverick fertility doctor who works under the radar with Jillian Hendricks, a cunning young scientist bent on making her mark--and seducing her boss. Claire, Robert, and Jillian work together to create the world's first baby with three genetic parents--an unprecedented feat that could eliminate inherited disease. But when word of their illegal experiment leaks to the wrong person, Robert escapes into hiding with the now-pregnant Claire, leaving Jillian to serve out a prison sentence that destroys her future. Ten years later, a spunky girl named Abigail begins to understand that all is not right with the reclusive man and woman she knows as her parents. But the family's problems are only beginning. Jillian, hardened by a decade of jealousy and loss, has returned--and nothing will stop her from reuniting with the man and daughter who should have been hers" --